A facile rheological approach for the determination of "super toughness point" of nylon1212/POE-g-MAH/MWCNT nanocomposites. (16th June 2019) - Lv, Fucheng; Wang, Yifei; Song, Yao; Yang, Yanyu; Wang, Jianfeng; Cao, Yanxia; Li, Chenlin; Wang, Wanjie
Abstract: Toughness is an important parameter to evaluate the properties and determine the applicants of polymer/CNT nanocomposites. This study applies a rheological method to perform fast determination of the optimal mechanical properties and prediction of the conductive percolation regions of a polymer/CNT nanocomposite. The tunable mechanical and electrical properties of nylon1212/multi-walled carbon nanotube (MWCNT) nanocomposites with and without poly (ethylene-octene)-g-maleic anhydride (POE-g-MAH) are evaluated. Results indicate that three types of nanocomposites exhibit remarkable gel plateau in the dynamic rheological curves and their gel points change slightly. The introduction of POE-g-MAH can improve the notched Izod impact strength (NIIS) of nylon1212/MWCNT nanocomposites greatly. NIIS of all three nanocomposites first increase and then decrease with the MWCNT loading increasing. The gel points for three nanocomposites are related to the super-toughness points and located in the conductive percolation regions, indicating that the dynamic rheology can effectively determine the super-toughness points and predict the conductive percolation regions of nylon1212/MWCNT nanocomposites. Furthermore, the morphologies for three nanocomposites at the gel points unveil the new synergistic toughening mechanism. This study brings new insights for controlling the structures, properties and compound designs of polymer/CNT nanocomposites.